Experimental Persistent Infection of BALB/c Mice with Small-Colony Variants of Burkholderia pseudomallei Leads to Concurrent Upregulation of PD-1 on T Cells and Skewed Th1 and Th17 Responses. - Jia-Xiang See; Chandramathi Samudi; Alireza Saeidi; Nivedita Menon; Leang-Chung Choh; Jamuna Vadivelu; Esaki M Shankar (Public Library of Science (PLoS), 2016)
Burkholderia pseudomallei (B. pseudomallei), the causative agent of melioidosis, is a deadly pathogen endemic across parts of tropical South East Asia and Northern Australia. B. pseudomallei can remain latent within the intracellular compartment of the host cell over prolonged periods of time, and cause persistent disease leading to treatment difficulties. Understanding the immunological mechanisms behind persistent infection can result in improved treatment strategies in clinical melioidosis.Ten-day LD50 was determined for the small-colony variant (SCV) and its parental wild-type (WT) via intranasal route in experimental BALB/c mice. Persistent B. pseudomallei infection was generated by administrating sub-lethal dose of the two strains based on previously determined LD50. After two months, peripheral blood mononuclear cells (PBMCs) and plasma were obtained to investigate host immune responses against persistent B. pseudomallei infection. Lungs, livers, and spleens were harvested and bacterial loads in these organs were determined.Based on the ten-day LD50, the SCV was ~20-fold less virulent than the WT. The SCV caused higher bacterial loads in spleens compared to its WT counterparts with persistent B. pseudomallei infection. We found that the CD4+ T-cell frequencies were decreased, and the expressions of PD-1, but not CTLA-4 were significantly increased on the CD4+ and CD8+ T cells of these mice. Notably, persistent infection with the SCV led to significantly higher levels of PD-1 than the WT B. pseudomallei. Plasma IFN-γ, IL-6, and IL-17A levels were elevated only in SCV-infected mice. In addition, skewed plasma Th1 and Th17 responses were observed in SCV-infected mice relative to WT-infected and uninfected mice.B. pseudomallei appears to upregulate the expression of PD-1 on T cells to evade host immune responses, which likely facilitates bacterial persistence in the host. SCVs cause distinct pathology and immune responses in the host as compared to WT B. pseudomallei.